Impact of bottle size on in-home consumption of sugar-sweetened beverages: protocol for a feasibility and acceptability study. Issue 1 (December 2015) - Mantzari, Eleni; Hollands, Gareth; Pechey, Rachel; Jebb, Susan; Marteau, Theresa
Abstract Background Intake of free sugars in the population exceeds recommendations, with the largest source in the diet being sugar-sweetened beverages (SSBs). SSB consumption is linked to adverse health consequences and contributes to health inequalities, given greater consumption amongst the most deprived. One possible intervention is to reduce the available sizes of SSB packaging but there is an absence of evidence that this would reduce consumption. Based on evidence from studies targeting food consumption that people consume less when exposed to smaller package sizes, we hypothesise that presenting SSBs in smaller containers reduces consumption. We are planning a crossover randomised controlled trial to assess the impact of presenting a fixed volume of SSB in different bottle sizes on consumption at home. To reduce the uncertainties related to this trial, we propose a preliminary study to assess the feasibility and acceptability of the recruitment, allocation, measurement, retention and intervention procedures. Methods/design Households which purchase at least 2 l of regular cola drinks per week and live in Cambridgeshire, UK will have a set amount of a cola SSB (based on their typical weekly purchasing of cola) delivered to their homes each week by the research team. This total amount of cola will be packaged into bottles of one of four sizes: (i) 1500 ml, (ii) 1000 ml, (iii) 500 ml or (iv) 250 ml. A crossover design will be used in which households will each receive all four of the week-long interventions (the four different bottle sizes) over time, randomised in their order of presentation. Approximately 100 eligible households will be approached to assess the proportion interested in actively participating in the study. Of those interested, 16 will be invited to continue participation. Discussion The findings will inform the procedures for a crossover randomised controlled trial assessing the impact of presenting a fixed volume of SSB in different bottle sizes on consumption at home. The findings from such a trial are expected to provide the best estimate to date of the effect of container size on beverage consumption and inform ongoing scientific and policy discussions about the effectiveness of this intervention at reducing population intake of free sugars in beverages. Trial registration ISRCTN14964130